Study of a preoperative scoring system to predict difficult laparoscopic cholecystectomy - Md Ashraf Ali; Md Masleh Uddin; Md Nehal Ahmad; Shakil Jawed (Journal of Surgery and Surgical Research - Peertechz Publications, 2021)
Introduction: Laparoscopic Cholecystectomy (LC), one of the most commonly performed surgical procedures worldwide, is accepted as the gold standard in the treatment of symptomatic gallstones. Generally laparoscopic cholecystectomy has low incidence of morbidity, mortality and conversion rate to open surgery, but occasionally surgeons encountered difficulty while doing Laparoscopic cholecystectomy. Preoperative prediction of "difficult Laparoscopic cholecystectomy" improve the patient safety as well as useful in reducing the cost of therapy.  Aim: To study a scoring system based on various risk factors to preoperatively predict difficult Laparoscopic cholecystectomy. Materials & method: This study was conducted in Department of General surgery, Nalanda Medical College And Hospital Patna & associated All India Institute of Medical Science Patna. A total of 105 patients were included in this study. There are total 15 score from history, clinical & sonological findings. They were evaluated & scored on the basis of scoring system. Score upto 5 is defined as easy, 6-10 as difficult and 11-15 as very difficult. Result: Prediction comes true in 96.6% for easy, 87.8% for difficult & 60% for very difficult cases. Area under ROC curve is 0.96 and conversion rate is 3.8 in our study. Age >50 years, Male sex, H/o of hospitalisation due to acute cholecystitis, Palpable gallbladder, BMI >27.5, Abdominal scar, Thick walled GB (>4mm), and Pericholecystic collection were found to be significant predictive factors for difficult laparoscopic cholecystectomy. Conclusion: With the help of preoperative prediction, high risk patients may be informed & counseled before about probability of open conversion & difficulty in laparoscopic cholecystectomy.